A family affair? Long-term economic and mental health effects of spousal cancer - Böckerman, Petri; Kortelainen, Mika; Salokangas, Henri; Vaalavuo, Maria (Springer Nature, 2025)
Research on the family spillover effects of health shocks, which has focused mainly on labor market outcomes, has yielded inconclusive results, with limited insight into long-term consequences or underlying mechanisms. We analyze the short- and long-term impacts of cancer on the unaffected spouse's labor supply and mental health as well as marital stability, considering gender and relative income status within the households. Using population-based register data from Finland (1995-2019) and a dynamic difference-in-differences design, we observe two key findings. First, a cancer diagnosis leads to very modest changes in a spouse's labor supply but significant increases in the likelihood of psychotropic drug use and psychiatric outpatient visits. Second, the main results mask considerable heterogeneity regarding relative income within the household. Secondary earners increase their labor supply in response to fatal cancers but decrease it in non-fatal cases, while breadwinners show small negative responses in both. Bereaved women with lower income share experience more psychiatric symptoms, a trend not observed in men. Our findings reveal the importance of pre-shock breadwinner status in family responses to health shocks, suggesting the need for targeted support for caregiving and bereaved spouses.